(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2023)
The present paper proposes a reflection on the costume collection belonging to the University Theatre (TU) of the Federal University of Minas Gerais (UFMG) and on its intrinsic performativity by seeking to extract from the set that these collections create —both of photographs and costumes —strategies for the analysis of clothing categories. This piece of research approaches the complexity of cataloguing costume collections and thereby opens up some of the different potential memories associated to and enabled by these collections. In order to understand the referred material, we have sought to apply the concept of memory, according to its development by Paul Ricoeur in his book Memory, History, Forgetting, as well as Pierre Nora’s idea of memory(as explained in Entre Memória e História: A problemática dos lugares).In this way, we aim to discuss the notion of classification as well as the relation between History and Memory itself.